Effect of Shoot Age, Liming and Potassium Application for Summer Season Lac Cultivation on Butea monosperma Trees - Ghosal, S. (Indian Forester, 2017)
An experiment comprising levels of liming (liming and no liming), potassium application (0, 500 and 1000 g/tree) and shoot age was conducted in the research farm of Indian Institute of Natural Resins and Gums, Ranchi during 2011-12 to 2013-14 replicated five times to study the effect of soil fertility on rangeeni lac yield in the summer season on medium sized trees. Findings of the experiment indicated that lac yield ratio obtained in liming was 71 percent higher compared to no liming in case of 6 months age of shoots. However, analysis of data revealed that liming has got least effect on older shoots. Its effect was also reflected on yield attribute like sticklac yield. Increased soil fertility due to liming might have supplied better nutrition to the host and the host in turn could supply better nutrition to the insect. Lac yield increased significantly (4 to 7 times) if cultivation is done in older shoots. Interaction effect of liming and potassium was found to be significant in case of 6 months old shoots. Effect of potassium application was observed in the absence of liming and the highest dose could increase lac yield 2.8 times than that of control on six months old shoots. Similarly, liming in the absence of potassium application proved to be the best treatment. Applied potassium might have facilitated host to support nutrition of lac insect in a better way which ultimately increased lac yield.